STUDI TERHADAP PESERTA DIDIK MENGALAMI KECEMASAN SOSIAL SISWA KELAS X SMAN 1 SUNGAI RAYA - Hamid, Syarif Abdurahman; Yuline, Yuline; Halida, Halida (Universitas Tanjungpura, 2025)
This study aims to find out students who experience anxiety social in high school. The data source of this study is two participants class X students of SMA Negeri 1 Sungai Raya which is determined through purposive techniques Sampling. The method used is qualitative descriptive with techniques or instruments Data collection in the form of interviews, observations and documentation. Data analysis using an interactive model consisting of data reduction stages, data presentation and drawing conclusions. The results of the study show the characteristics of social anxiety, namely Students are passive in following the learning process in the classroom, feel afraid and trembling when advancing in front of the class, speaking often stammering and diverting The view of the interlocutor, not wanting to be negatively evaluated, the level of confidence low, easy to panic and lose focus, many reasons if you are not ready to appear in front class, avoiding responsibility, and do not want to be the center of attention in the classroom. Internal factors that cause social anxiety are introverted personalities, mental weak, unconfident, unable to face problems and avoiding, likes daydreaming and daydreaming excessively and past traumas. For external factors, namely overprotective parents, lack of support and attention from the family, and poor social environment. The impact of social anxiety is difficult interacting, poor academic career not having many friends, decreased functioning social roles, behavioral barriers and poor mentality.